Injeção de ar via irrigação por gotejamentos superficial e subsuperficial na cultura da alface - Gomes, Gabriel Perin [UNESP] (2015)
São Paulo State has the largest production of the vegetable sector of Brazil, 20% of production and the main consumer market, 22% of the population. With the water crisis present in our day by day, are seen the importance of adequate water use in olericulture, activity that requires intensive soil management, use of fertilizers and irrigation water. To improve the irrigation water use efficiency, it is necessary to intensify the research and development of new technologies. This study aimed to evaluate the influence of air injection through irrigation by surface and subsurface drip in the development of lettuce, where water depths were based through tensiometry. The experiment was conducted in a greenhouse located in the Faculdade de Ciências Agronômicas, UNESP - Univ Estadual Paulista, Campus Botucatu, Departamento de Engenharia Rural. Was used the experimental design was a randomized block design (RBD) in factorial 2 x 2, being the first factor irrigation (surface and subsurface drip) and the second factor aeration (with and without air injection), were performed five evaluations throughout the cycle, using three plants like repeats in each of the 20 plots, in two separate tests. The first test had 16 plots for evaluation of plant parameters and the second test with the remaining four plots with the same treatment from others, however, were used only for production parameter at the last valuation date. Two cycles were conducted for finding and validation of the effect of the air injection into the culture. For treatment with air injection we used a Venturi injector type injector ¾. We evaluated the number of leaves, fresh and shoot dry, stem diameter, fresh and dry weight of roots, root length, root volume and content of macro and micronutrients. The data were subjected to analysis of variance by Tukey test at 5% probability. In the first cycle, although no significant difference, but the ...